The Role of Natural Hierarchy in Obtaining Happiness in Faraby's View (Raparin Journal of Humanities (RJH), 2022)
True happiness in Farabi’s vision, in terms of nature and of itself, is a great and promising virtue and it is the main objective in the life of the Virtuous City and the value of it results in lasting permanently as an objective and never becomes a mean. The project and basis of Farabi’s view relates to the establishment of significant means and methods for happiness attainment. The first assistive mean is to gather around the structure of the city and society. He views society as an organic system, though they differ in duty and rank, but they own cooperation basis between them. The flawless image of society is revealed only when it is ruled over by the president of an active mind. The conclusion of combined means brings about the foundation of the Virtuous City which is the only place for happiness attainment.The absence of collaboration, cooperation and hierarchy, lack of active mind of the president, and ignorance towards the true happiness by the individuals, are those features which Farabi counts as the contraries to the Virtuous City, the objective of this process is to prove that no city and crowd is capable of being happy if they do not place the ways and nature of the Virtuous City to their being.Available research by using descriptive and analytical method for the purpose of Faraby's view on obtaining happiness and a desirable society through simile and finding the connection between the city of goodness and and human nature to be represented, and for this, it will reach the conclusion that human gathering in the framework of the society, considering the natural hierarchy, and cooperation for providing happiness.